Implementation of NXT 2.0 Mindstorm Robot Sensors on Mobile Education for Students - Kuncoro, Rizki Danang Kartiko; Arifudin, Riza; Sugiharti, Endang (Universitas Muhammadiyah Surakarta, 2018)
In the current 4.0 industry era, technological development is very fast and fast. In the world of education the lessons about technology should have been introduced to students since elementary school. Do not have to use complex technology, enough to use robotics technology from the NXT 2.0 LEGO minstorm robot which is lego-based to play and learn algorithms in composing technology. Using this tool can also be controlled by the smartphone application. Using a mobile application that we designed will make it easier for students to use and play this educational media. In this media, each sensor in the robot will be interrelated to the mobile control, we have tested this control with 83.33% detection accuracy. So that it can effectively become an interactive and fun technology-based learning media for students. The purpose of this educational media is to improve the quality of education in Indonesia so that it can be technology-based and enjoyable for students. Because the application of technology to education is very important to hone the power of creative thinking in composing programming algorithms using robots. Students will be very interested and have good enthusiasm in learning robotics based on this mobile application.